2007
DOI: 10.2337/dc07-0318
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan Shows an Equivalent Effect of Vitamin C in Further Improving Endothelial Dysfunction After Glycemia Normalization in Type 1 Diabetes

Abstract: OBJECTIVE -Long-lasting hyperglycemia in type 1 diabetic patients induces permanent alterations of endothelial function by increased oxidative stress, even when glycemia is normalized.RESEARCH DESIGN AND METHODS -In this study, 36 type 1 diabetic patients and 12 control subjects were enrolled. The diabetic patients were divided into three groups. The first group was treated for 24 h with insulin, achieving a near normalization of glycemia. After 12 h of this treatment, vitamin C was added for the remaining 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
5
21
0
Order By: Relevance
“…Our results are in agreement with those of previous studies showing that short-term (4-12 weeks) treatment with telmisartan improved endothelial function in patients with essential hypertension and diabetes. 24,27,28 In addition to the previous shortterm observations, 24,27,28 we clearly showed the markedly beneficial effect on endothelial function after long-term (1-year) treatment with telmisartan. Furthermore, our study showed for the first time that the improvement in FMD correlated with the reduction in blood pressure and the increase in circulating AN after treatment with telmisartan.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are in agreement with those of previous studies showing that short-term (4-12 weeks) treatment with telmisartan improved endothelial function in patients with essential hypertension and diabetes. 24,27,28 In addition to the previous shortterm observations, 24,27,28 we clearly showed the markedly beneficial effect on endothelial function after long-term (1-year) treatment with telmisartan. Furthermore, our study showed for the first time that the improvement in FMD correlated with the reduction in blood pressure and the increase in circulating AN after treatment with telmisartan.…”
Section: Discussionsupporting
confidence: 81%
“…It is tempting to speculate that the anti-inflammatory and antiatherosclerotic effects of telmisartan may contribute to the improvement of endothelial function by increased AN and decreased oxidative stress. 28 There are several limitations in this study. First, it is an open-label study that did not use a placebo or specify other antihypertensive drugs for comparison.…”
Section: Discussionmentioning
confidence: 92%
“…Accumulation of nitrotyrosine has been documented in vascular endothelium (58,63), heart (57,58), retina (27,52), and kidney (25) of STZ-diabetic rodents as well as circulation (11,10,34), cutaneous vasculature (64), myocardium (32), and kidney (66) of human subjects with diabetes mellitus. In peripheral nervous system, increased nitrotyrosine immunoreactivities have been identified in the sciatic nerve, gray matter of spinal cord, DRG, and vasa nervorum of STZ-diabetic rats and mice, Zucker fatty rats, and Zucker diabetic fatty rats as well as leptin-deficient (ob/ob) and high-fat diet-fed mice (13,16,24,26,48,51,52,54,60,69).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the important role of nitrosative stress in diabetic neuropathy in humans is emerging. Increased plasma nitrotyrosine levels have been found to correlate with redistribution of sudomotor responses, an early sign of sympathetic nerve dysfunction, as well as with endothelial dysfunction, an important player in PDN (9,37), in type 1 diabetic subjects (11,10,34).…”
Section: Discussionmentioning
confidence: 99%
“…Although the important role of oxidative stress in type 1 peripheral diabetic neuropathy (PDN) is well established (2)(3)(4), the contribution of the nitrosative component of free radical and oxidant-induced injury, and, in particular, of the highly reactive oxidant peroxynitrite (5), to diabetes-associated neuropathic changes has not been properly explored. Recent clinical studies revealed increased plasma nitrotyrosine levels and their correlation with endothelial dysfunction and redistribution of sudomotor responses, an early sign of sympathetic nerve dysfunction, in type 1 diabetic subjects (6,7). Furthermore, plasma peroxynitrite generation assessed by the pholasin chemiluminescence test correlated with the diabetic neuropathy impairment score of the lower limbs (8).…”
Section: Introductionmentioning
confidence: 99%